Sikap Masyarakat Lampung terhadap Bahasa Nenek Moyang - Windo Dicky Irawan (Edukasi Lingua Sastra, 2017)
This paper focuses on the attitude of the native language speakers of Lampung. This study describes the attitude of the language of the people of Lampung to the language of his ancestors. The results of the study found that all respondents were not embarrassed to use their local language in their own areas, but 15% of respondents were embarrassed to use local language outside Lampung. Based on the integrative function, there is a tendency of people in Lampung to have a positive attitude towards their language. Meanwhile, with reference to the instrumental function, there is a tendency that they have a negative attitude towards language and a positive attitude towards Bahasa Indonesia.